Keterampilan Guru Dalam Mengelola Pembelajaran Dengan Menggunakan Artificial Intelligence (Kecerdasan Buatan) Di MTs DDI Lapeo - Nur Ainun Amalia B Ayi; Abd Haling; Andromeda Valentino Sinaga (Universitas Hamzanwadi, 2025)
Digital technology transformation has introduced new paradigms in education through artificial intelligence integration becoming integral components of contemporary learning processes. This research aims to describe teachers' skills in managing learning using artificial intelligence at MTs DDI Lapeo and analyze its impact on learning management capabilities. The research method employed qualitative approach with case study design, involving 11 informants consisting of principal, five teachers, and five students. Data collection was conducted through triangulation techniques of participative obswwervation, in-depth interviews, and documentation. Data analysis utilized Miles and Huberman model with validity ensured through member check and source triangulation. Research findings identified six dimensions of teachers' skills in managing AI-based learning: AI implementation in learning processes, AI operational skills, personalized learning, smart content development, AI chatbot integration, and AI-based learning evaluation. Findings revealed 73.08% teachers have utilized AI platforms such as ChatGPT and Gemini AI. AI implementation impacts include substantial administrative efficiency improvement and significant teacher workload reduction. AI enables personalized learning responsive to individual student needs, creates interactive smart content, and facilitates evaluation accommodating digital native characteristics. Transformative AI implementation in education requires adequate infrastructure support and continuous digital competency development for 21st-century learning optimization.